High-performance solar structural sealant and preparation method thereof

By using homemade side chain length alkyl polyalkoxy water-resistant additives and other components in solar structure sealants, the problem of easy cracking, embrittlement and powdering of sealants in high temperature and high humidity environments is solved, and the preparation of high-performance sealants is achieved, with excellent durability and bonding strength.

CN119709109APending Publication Date: 2025-03-28CHENGDU GUIBAO SCI & TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411916550.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing solar structure sealants are prone to cracking, embrittlement, powdering, debonding and other problems in long-term high-temperature and high-humidity environments, and cannot effectively overcome the test of harsh environments.

Method used

Using homemade polyalkoxy water-resistant additives with side chain length alkyl, combined with hydroxyl-terminated polydimethylsiloxane, calcium carbonate, gas-phase white carbon black and other components, a high-performance solar structure sealant is formed through specific formulation and preparation processes.

Benefits of technology

It significantly improves the durability and bonding strength of sealants in high temperature and high humidity environments, avoids cracking, embrittlement and powdering, and meets the requirements of strict glue use in photovoltaic buildings and other rigorous glue use areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaic structural sealants, and discloses a high-performance solar structural sealant and a preparation method of the high-performance solar structural sealant. Comprising the following components in parts by weight: 40-70 parts of hydroxyl-terminated polydimethylsiloxane, 20-60 parts of calcium carbonate, 0-20 parts of fumed silica, 3-12 parts of an alcohol type cross-linking agent, 3-10 parts of a silane coupling agent, 0.1-1 part of a catalyst, 1-2 parts of a pigment and 5-20 parts of a polyalkoxy water-resistant aid with a long alkyl side chain. The high-performance solar structural sealant prepared by the invention has long-term damp-heat aging resistance, is suitable for bonding of structures such as photovoltaic building integration, photo-thermal and buildings, and meets the requirement of using the sealant in a long-term outdoor harsh environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaic structural sealants, and in particular to a high-performance solar structural sealant and a preparation method thereof. Background Art

[0002] In recent years, clean energy such as solar energy has developed rapidly. Among them, photovoltaic power generation occupies an important position in clean energy with its incomparable cost advantage. Photovoltaic power generation mainly includes two operating modes: centralized photovoltaic power stations and "photovoltaic + building" distributed power generation. Among them, photovoltaic power stations mainly use idle land resources such as deserts and are the main force of the current photovoltaic power generation model, but they also have disadvantages such as long cross-regional transmission distances, large losses, and high maintenance costs. "Photovoltaic + building" distributed power generation not only avoids the problem of long-distance transmission of centralized photovoltaic power stations, but also effectively reduces cleaning and maintenance costs due to relatively good construction environment conditions. It is an effective supplementary measure for power consumption centers with high demand for electricity.

[0003] At present, there are two main ways to connect photovoltaic modules to buildings: a mechanical connection mode with an all-metal bracket and a flexible connection mode with a structural adhesive connection. Among them, the flexible connection overcomes the shortcomings of stress concentration in mechanical connection, heavy load on metal structures, and easy corrosion at the connection points, further improving the safety and service life of the modules. Silicone structural adhesive is undoubtedly the best choice for the development of solar structural sealants in terms of structural stability and long-term weather resistance. However, unlike ordinary building silicone structural adhesives, the exterior of solar structural adhesives is not protected by weather-resistant adhesives, and its design adds more non-facade structures, making it easier for water vapor to accumulate. Coupled with the heating and light factors of the module operation, the entire module is in a high temperature and high humidity environment for a long time, making the structural adhesive more prone to aging, cracking, and bonding failure. Obviously, the current building structural adhesive cannot overcome the above harsh environmental tests. Therefore, it is urgent to develop a method that can maintain good bonding strength in a high temperature and high humidity environment for a long time to avoid problems such as cracking, embrittlement, and powdering. Summary of the invention

[0004] The present invention aims to provide a high-performance solar structural sealant and a preparation method thereof, so as to solve the problems that existing silicone products are prone to cracking, embrittlement, powdering and debonding in a long-term high-humidity and high-heat environment.

[0005] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a high-performance solar structural sealant, characterized in that: calculated by mass, it includes 40 to 70 parts of end-hydroxyl-terminated polydimethylsiloxane, 20 to 60 parts of calcium carbonate, 0 to 20 parts of fumed silica, 3 to 12 parts of alcohol-type crosslinking agent, 3 to 10 parts of silane coupling agent, 0.1 to 1 part of catalyst, 1 to 2 parts of pigment, and 5 to 20 parts of polyalkoxy water-resistant additive with long side chain alkyl.

[0006] Preferably, as an improvement, the viscosity of the polyalkoxy water-resistant additive with a long alkyl side chain is 100 to 500 mPa·s at 25° C., and the structure of the polyalkoxy water-resistant additive with a long alkyl side chain is as shown in formula (I):

[0007]

[0008] In formula (I), a is an integer between 20 and 150, b is an integer between 15 and 30, n is an integer between 5 and 20, and n<b.

[0009] Preferably, as an improvement, the R1 group of the polyalkoxy water-resistant additive with a long alkyl side chain is a methyl group, R2 and R3 are obtained by hydrosilylation of a side hydrogen-containing silicone oil with a long chain olefin or vinyl silane; R2 is of formula (II) or (III); and R3 is one or more of formulas (IV) to (XII):

[0010]

[0011]

[0012] Preferably, as an improvement, the viscosity of the hydroxyl-terminated polydimethylsiloxane is 20000-80000 mPa·s.

[0013] Preferably, as an improvement, the calcium carbonate is light calcium carbonate, and the average particle size of the light calcium carbonate is 40 to 80 nm; the fumed silica is divided into hydrophilic silica or hydrophobic silica.

[0014] Preferably, as an improvement, the alcohol-type crosslinking agent is at least one of methyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, ethyl orthosilicate, propyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and octyltrimethoxysilane, and the purity of the alcohol-type crosslinking agent is ≥99%.

[0015] Preferably, as an improvement, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0016] Preferably, as an improvement, the catalyst is at least one of dibutyltin dilaurate, dioctyltin dilaurate and dibutyltin dicaprate; and the pigment is titanium dioxide paste or carbon black paste.

[0017] Preferably, as an improvement, a method for preparing a high-performance solar structural sealant comprises the following steps:

[0018] Step 1, mixing hydroxyl-terminated polydimethylsiloxane, calcium carbonate and fumed silica and stirring to obtain a mixture;

[0019] Step 2: the mixed material obtained in step 1 is discharged after being shoveled, dehydrated at high temperature, and stirred evenly to obtain a single-component glue base material;

[0020] Step 3: Evenly stir the base material in step 2 with the cross-linking agent, the silane coupling agent, the polyalkoxy water-resistant additive with a long alkyl side chain, and the catalyst to obtain a high-performance solar structural sealant.

[0021] Preferably, as an improvement, the stirring processes in step 2 and step 3 are both carried out under vacuum conditions; in step 3, the preparation method of the polyalkoxy water-resistant additive having a long alkyl side chain comprises the following steps:

[0022] S1. Add appropriate amount of toluene and catalyst chloroplatinic acid into hydrogen-containing silicone oil;

[0023] S2. Raise the temperature to 100-110°C, slowly drop vinyltrimethoxysilane and 1-tetradecene under stirring or reflux;

[0024] S3. Separation: remove the solvent by distillation under reduced pressure.

[0025] The principles and advantages of this solution are: in actual application, in this technical solution, the formula and preparation process of the sealant are comprehensively upgraded to address the problems of cracking, embrittlement, powdering, and debonding that silicone products in the prior art are prone to in a long-term high temperature and high humidity environment. First, the inventors conducted a reverse analysis of the above technical problems: single-component sealants are gradually cured from the outside to the inside, and water vapor is required to participate in the curing process to produce cross-linking. After curing, it is necessary to reduce the entry of water vapor as much as possible to ensure that the sealant can withstand high temperature and high humidity aging for a long time. How to combine these two opposite processes to ensure both normal curing of the sealant and long-term resistance to moisture and heat aging is the key to overcoming this problem in the field. Based on this, in terms of formula composition, this technical solution adopts a self-made polyalkoxy water-resistant additive with a long alkyl side chain. On the one hand, the polyalkoxy water-resistant additive with a long alkyl side chain has an alkoxy structure (group R3) and can participate in the cross-linking reaction without affecting the curing speed and self-strength of the colloid; on the other hand, the polyalkoxy water-resistant additive with a long alkyl side chain increases the hydrophobic component in the structural adhesive by introducing a long carbon chain structure (group R2), which can effectively improve the barrier effect of the structural adhesive on water vapor after curing, thereby meeting the requirements of the long-term moisture and heat aging resistance of the adhesive in the harsh adhesive fields such as photovoltaic buildings. In addition, R2 and R3 in the polyalkoxy water-resistant additive with a long alkyl side chain are obtained by the addition of hydrosilylation of side hydrogen silicone oil with long-chain olefins and vinyl silane. The silicone oil has a long-chain alkane structure, increased steric hindrance and good compatibility, which can effectively reduce the cross-linking density of the glue during the curing process, thereby giving the glue excellent elongation and improving the elasticity of the sealant. DETAILED DESCRIPTION

[0026] The following is further described in detail through specific implementations, but the implementation of the present invention is not limited thereto. Unless otherwise specified, the technical means used in the following implementations are conventional means well known to those skilled in the art; the experimental methods used are all conventional methods; the materials, reagents, etc. used can all be obtained from commercial channels.

[0027] Program Overview:

[0028] A high-performance solar structural sealant comprises, by weight, 40-70 parts of hydroxyl-terminated polydimethylsiloxane, 20-60 parts of calcium carbonate, 0-20 parts of fumed silica, 3-12 parts of alcohol-type crosslinking agent, 3-10 parts of silane coupling agent, 0.1-1 part of catalyst, 1-2 parts of pigment and 5-20 parts of polyalkoxy water-resistant additive with long alkyl side chain.

[0029] The viscosity of the hydroxyl-terminated polydimethylsiloxane is 10000-100000 mPa·s, preferably 20000-80000 mPa·s.

[0030] The calcium carbonate is light calcium carbonate, specifically nano-active calcium carbonate, and the average particle size of the nano-active calcium carbonate is 40 to 80 nm.

[0031] Fumed silica is classified as either hydrophilic silica or hydrophobic silica.

[0032] The alcohol type crosslinking agent is a commercially available alkoxysilane crosslinking agent, specifically at least one of methyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, ethyl orthosilicate, propyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and octyltrimethoxysilane.

[0033] The silane coupling agent is at least one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

[0034] The catalyst is an organic tin catalyst, and specifically at least one of dibutyltin dilaurate, dioctyltin dilaurate and dibutyltin dicaprate can be selected.

[0035] The pigment is titanium dioxide paste or carbon black paste.

[0036] The viscosity of the polyalkoxy water-resistant additive with a long alkyl side chain is 100-500 mPa·s at 25°C. The structure of the polyalkoxy water-resistant additive with a long alkyl side chain is as shown in formula (I):

[0037]

[0038] In formula (I), a is an integer between 20 and 150, b is an integer between 15 and 30, n is an integer between 5 and 20, and n<b; R1 is a methyl group, R2 and R3 are obtained by hydrosilylation of side hydrogenated silicone oil with long-chain olefins and vinyl silane; R2 is formula (II) or formula (III); R3 is one or more of formula (IV) to formula (XII).

[0039]

[0040]

[0041] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0042] Step 1, mixing hydroxyl-terminated polydimethylsiloxane, calcium carbonate and fumed silica and stirring to obtain a mixture;

[0043] Step 2: the mixed material obtained in step 1 is subjected to shoveling, high-temperature dehydration, and stirring under vacuum conditions to obtain a glue base material;

[0044] Step 3: Stir the base material in step 2 with the cross-linking agent, the silane coupling agent, the polyalkoxy water-resistant additive with a long alkyl side chain, and the catalyst under vacuum conditions to obtain a high-performance solar structural sealant;

[0045] The preparation method of a polyalkoxy water-resistant additive having a long alkyl side chain comprises the following steps:

[0046] S1. Add appropriate amount of toluene and catalyst chloroplatinic acid into hydrogen-containing silicone oil;

[0047] S2. Raise the temperature to 100-110°C, slowly drop vinyltrimethoxysilane and 1-tetradecene under stirring or reflux;

[0048] S3. Separation: remove the solvent by distillation under reduced pressure.

[0049] Example 1

[0050] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0051] Step 1: Add 40 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 20 parts of calcium carbonate, and 20 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0052] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 20 parts of 10000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0053] Step 3: Prepare 5 parts of vinyl triethoxysilane, 7 parts of phenyl triethoxysilane, 2 parts of γ-aminopropyl triethoxysilane, 3 parts of 3-(2-aminoethyl)aminopropyl triethoxysilane, 5 parts of γ-(2,3-epoxypropoxy)propyl trimethoxysilane, 5 parts of polyalkoxy water-resistant additives with long side chain alkyl groups (as shown in the following formula ①, a=40, n=10, bn=5, and the viscosity of silicone oil is 100mPa·s), 1 part of carbon black, and 0.1 part of dioctyltin dilaurate, start the vacuum pump of the reactor, and open the vacuum valve to evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, and stir in vacuum for 25 minutes to obtain a high-performance solar structural sealant.

[0054]

[0055] The preparation method of a polyalkoxy water-resistant additive having a long alkyl side chain of formula ① comprises the following steps:

[0056] S1. Add the calculated amount of hydrogenated silicone oil into a dry four-necked flask, add an appropriate amount of toluene and a calculated amount of catalyst chloroplatinic acid;

[0057] S2, raising the temperature (100-110° C.), slowly dropping vinyltrimethoxysilane and 1-tetradecene under stirring or reflux, the reaction formula of the target product is shown in Formula (XIII);

[0058] S3. Separation: remove the solvent by distillation under reduced pressure.

[0059]

[0060] Comparative Example 1

[0061] The difference between this comparative example and Example 1 is that in this comparative example, the water-resistant additive in Example 1 is replaced by an equal amount of 100 mPa·s dimethyl silicone oil.

[0062] Example 2

[0063] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0064] Step 1: Add 40 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 60 parts of calcium carbonate, and 10 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0065] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 30 parts of 20000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0066] Step 3: Prepare 7 parts of vinyl triethoxysilane, 3 parts of phenyl triethoxysilane, 2 parts of γ-glycidyloxypropyl triethoxysilane, 3 parts of γ-aminoethylaminopropyl trimethoxysilane, 2 parts of γ-(2,3-epoxypropoxy)propyl trimethoxysilane, 8 parts of polyalkoxy water-resistant additives with long side chain alkyl (as shown in the following formula ②, a=150, n=10, bn=5, the viscosity of silicone oil is 500mPa·s), 2 parts of titanium dioxide paste, and 1 part of dibutyltin dilaurate, start the vacuum pump of the reactor, open the vacuum valve and evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, and keep the vacuum stirring for 25 minutes to obtain high-performance solar structure sealant.

[0067]

[0068] Comparative Example 2

[0069] The difference between this comparative example and Example 2 is that in this comparative example, the water-resistant additive in Example 2 is replaced by an equal amount of 500 mPa·s dimethyl silicone oil.

[0070] Example 3

[0071] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0072] Step 1: Add 10 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 20 parts of calcium carbonate, and 10 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0073] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 40 parts of 20000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0074] Step 3: Prepare 1 part of propyl trimethoxysilane, 1 part of octyl trimethoxysilane, 1 part of ethyl orthosilicate, 1 part of β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 2 parts of β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 20 parts of polyalkoxy water-resistant additives with long side chain alkyl groups (as shown in the following formula ③, a=150, n=5, bn=10, and the viscosity of silicone oil is 500mPa·s), 0.5 parts of dioctyltin dilaurate, and 0.1 parts of dibutyltin didecanoate, respectively, start the vacuum pump of the reactor, and open the vacuum valve to evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after the feeding is completed, and stir in vacuum for 25 minutes to obtain a high-performance solar structural sealant.

[0075]

[0076] Comparative Example 3

[0077] The difference between this comparative example and Example 3 is that in this comparative example, the water-resistant additive in Example 3 is replaced by an equal amount of 500 mPa·s dimethyl silicone oil.

[0078] Example 4

[0079] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0080] Step 1: Add 40 parts of 20000 mPa·s hydroxyl-terminated polydimethylsiloxane and 50 parts of calcium carbonate into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0081] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add the remaining 10 parts of 20000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0082] Step 3: Prepare 5 parts of vinyl triethoxysilane, 5 parts of phenyl triethoxysilane, 2 parts of γ-aminopropyl triethoxysilane, 3 parts of γ-aminoethylaminopropyl trimethoxysilane, 2 parts of γ-(2,3-epoxypropoxy)propyl trimethoxysilane, 5 parts of polyalkoxy water-resistant additives with long side chain alkyl groups (as shown in the following formula ④, a=70, n=20, bn=10, and the viscosity of silicone oil is 350mPa·s), and 1 part of dioctyltin dilaurate, start the vacuum pump of the reactor, and open the vacuum valve to evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, maintain vacuum and stir for 25 minutes to obtain a high-performance solar structural sealant.

[0083]

[0084] Comparative Example 4

[0085] The difference between this comparative example and Example 4 is that in this comparative example, the water-resistant additive in Example 4 is replaced by an equal amount of the additive of Formula 4-1.

[0086]

[0087] Example 5

[0088] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0089] Step 1: Add 30 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 40 parts of calcium carbonate, and 10 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0090] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 20 parts of 10000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0091] Step 3: Prepare 5 parts of vinyl triethoxysilane, 5-phenyl triethoxysilane, 2 parts of γ-aminopropyl triethoxysilane, 3 parts of γ-aminoethylaminopropyl trimethoxysilane, 2 parts of γ-(2,3-epoxypropoxy)propyl trimethoxysilane, 12 parts of polyalkoxy water-resistant additives with long side chain alkyl groups (as shown in the following formula ⑤, a=70, n=20, bn=10, and the viscosity of silicone oil is 350mPa·s), and 0.5 parts of dioctyltin dilaurate, start the vacuum pump of the reactor, and open the vacuum valve to evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, and stir in vacuum for 25 minutes to obtain a high-performance solar structural sealant.

[0092]

[0093] Comparative Example 5

[0094] The difference between this comparative example and Example 5 is that in this comparative example, the water-resistant additive in Example 5 is replaced by an equal amount of 350 mPa·s dimethyl silicone oil.

[0095] Example 6

[0096] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0097] Step 1: Add 30 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 30 parts of calcium carbonate, and 10 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0098] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 40 parts of 20000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0099] Step 3: Prepare 5 parts of vinyl triethoxysilane, 5 parts of methyl trimethoxysilane, 2 parts of γ-aminopropyl triethoxysilane, 3 parts of γ-aminoethylaminopropyl trimethoxysilane, 2 parts of γ-(2,3-epoxypropoxy)propyl trimethoxysilane, 20 parts of polyalkoxy water-resistant additive with long side chain alkyl (as shown in the following formula ⑥, a=20, n=5, bn=20, the viscosity of silicone oil is 350mPa·s), and 0.8 parts of dioctyltin dilaurate, start the vacuum pump of the reactor, open the vacuum valve and evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, maintain vacuum and stir for 25 minutes to obtain high-performance solar structural sealant.

[0100]

[0101] Comparative Example 6

[0102] The difference between this comparative example and Example 6 is that in this comparative example, the water-resistant additive in Example 6 is replaced by an equal amount of 350 mPa·s dimethyl silicone oil.

[0103] Example 7

[0104] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0105] Step 1: Add 20 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 20 parts of calcium carbonate, and 20 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0106] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 30 parts of 20000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0107] Step 3: Prepare 4 parts of vinyl triethoxysilane, 6 parts of methyl trimethoxysilane, 3 parts of γ-aminopropyl triethoxysilane, 2 parts of γ-aminoethyl aminopropyl trimethoxysilane, 2 parts of γ-(2,3-epoxypropoxy) propyl trimethoxysilane, 20 parts of polyalkoxy water-resistant additives with long side chain alkyl groups (as shown in the following formula ⑦, a=150, n=10, bn=5, and the viscosity of silicone oil is 500mPa·s), and 0.8 parts of dioctyltin dilaurate, start the vacuum pump of the reactor, and open the vacuum valve to evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, and stir in vacuum for 25 minutes to obtain a high-performance solar structural sealant.

[0108]

[0109] Comparative Example 7

[0110] The difference between this comparative example and Example 7 is that in this comparative example, the water auxiliary agent in Example 7 is replaced by an equal amount of 500 mPa·s dimethyl silicone oil.

[0111] Example 8

[0112] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0113] Step 1: Add 20 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 50 parts of calcium carbonate, and 10 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0114] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 30 parts of 20000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0115] Step 3: Prepare 6 parts of vinyl triethoxysilane, 4 parts of methyl trimethoxysilane, 2 parts of γ-aminopropyl triethoxysilane, 3 parts of γ-aminoethyl aminopropyl trimethoxysilane, 2 parts of γ-(2,3-epoxypropoxy) propyl trimethoxysilane, 20 parts of polyalkoxy water-resistant additives with long side chain alkyl groups (as shown in the following formula ⑧, a=70, n=20, bn=10, and the viscosity of silicone oil is 350mPa·s), and 0.8 parts of dioctyltin dilaurate, start the vacuum pump of the reactor, and open the vacuum valve to evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, and stir in vacuum for 25 minutes to obtain a high-performance solar structural sealant.

[0116]

[0117] Comparative Example 8

[0118] The difference between this comparative example and Example 8 is that in this comparative example, the water-resistant additive in Example 8 is replaced by an equal amount of 350 mPa·s dimethyl silicone oil.

[0119] Example 9

[0120] A method for preparing a high-performance solar structural sealant comprises the following steps:

[0121] Step 1: Add 20 parts of 80000 mPa·s hydroxyl-terminated polydimethylsiloxane, 20 parts of calcium carbonate, and 10 parts of fumed silica into a planetary mixer in sequence, and stir at normal pressure for 20 minutes to obtain a mixture;

[0122] Step 2: After stopping the machine to scrape the edges, vacuumize and stir for 15 minutes under the condition of vacuum degree ≤-0.086MPa, stop the machine to add 30 parts of 20000mPa·s hydroxyl-terminated polydimethylsiloxane, keep the temperature above 110°C after this step, stir at normal pressure for 10 minutes, stop scraping the edges and vacuum stir for 3 hours, and obtain the glue base material after removing water;

[0123] Step 3: Prepare 4 parts of vinyl triethoxysilane, 4 parts of methyl trimethoxysilane, 3 parts of γ-aminopropyl triethoxysilane, 3 parts of γ-aminoethyl aminopropyl trimethoxysilane, 3 parts of γ-(2,3-epoxypropoxy) propyl trimethoxysilane, 20 parts of polyalkoxy water-resistant additives with long side chain alkyl (as shown in the following formula ⑨, a=40, n=10, bn=5, the viscosity of silicone oil is 100mPa·s), and 0.8 parts of dioctyltin dilaurate, start the vacuum pump of the reactor, open the vacuum valve and evacuate. Quickly draw each raw material into the reactor through negative pressure, close the feed valve after feeding, maintain vacuum and stir for 25 minutes to obtain high-performance solar structural sealant.

[0124]

[0125] Comparative Example 9

[0126] The difference between this comparative example and Example 8 is that in this comparative example, the water-resistant additive in Example 8 is replaced by an equal amount of 100 mPa·s dimethyl silicone oil.

[0127] Example

[0128] The high-performance solar structural sealants obtained in the above embodiments and comparative examples were tested for performance, and the specific testing method is as follows:

[0129] 1. Determine the tensile strength and elongation at break of structural adhesives according to the method specified in GB / T 528 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".

[0130] 2. Determine the tensile bond strength of structural adhesive in accordance with GB / T13477.8 "Test methods for building sealing materials Part 8: Determination of tensile adhesion".

[0131] 3. Humidity-heat test (DH2000) aging conditions: test temperature: (85±2)℃, relative humidity: (85±5)%, test time: 2000h.

[0132] The test was repeated three times for each group, and the results are shown in Tables 1 and 2: It can be seen from the performance data in Tables 1-2 that the high-performance solar structure sealant provided by the present invention has significantly improved resistance to moisture and heat aging compared with the comparative examples, which is specifically characterized by the tensile bonding strength and failure form of the glue before and after resistance to double moisture and heat aging, tensile strength and elongation at break.

[0133] Table 1 Performance Test of Examples 1-9

[0134]

[0135] Table 2 Performance test of comparative examples 1-9

[0136]

[0137]

[0138] The above is only an embodiment of the present invention, and the common knowledge such as the known specific technical solutions and / or characteristics in the solution is not described in detail. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the technical solution of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A high-performance solar structural sealant, characterized by: Calculated by mass, it includes 40-70 parts of terminal hydroxyl-terminated polydimethylsiloxane, 20-60 parts of calcium carbonate, 0-20 parts of fumed silica, 3-12 parts of alcohol crosslinking agent, 3-10 parts of silane coupling agent, 0.1-1 part of catalyst, 1-2 parts of pigment, and 5-20 parts of polyalkoxy water-resistant additive with long alkyl side chain.

2. A high performance solar structure sealant according to claim 1, characterized in that: The polyalkoxy water-resistant additive with a long alkyl side chain has a viscosity of 100 to 500 mPa·s at 25° C. The structure of the polyalkoxy water-resistant additive with a long alkyl side chain is as shown in formula (I): In formula (I), a is an integer between 20 and 150, b is an integer between 15 and 30, n is an integer between 5 and 20, and n <b。 3. A high performance solar structure sealant according to claim 2, characterized in that: The R1 group of the polyalkoxy water-resistant additive with a long side chain alkyl group is methyl, R2 and R3 are obtained by hydrosilylation of side hydrogen-containing silicone oil with long chain olefins and vinyl silane; R2 is formula (II) or formula (III); R3 is one or more of formula (IV) to formula (XII):

4. A high performance solar structure sealant according to claim 3, characterized in that: The viscosity of the hydroxyl-terminated polydimethylsiloxane is 20000-80000 mPa·s.

5. A high performance solar structure sealant according to claim 4, characterized in that: The calcium carbonate is light calcium carbonate, and the average particle size of the light calcium carbonate is 40-80 nm; the fumed silica is divided into hydrophilic silica or hydrophobic silica.

6. A high performance solar structure sealant according to claim 5, characterized in that: The alcohol crosslinking agent is at least one of methyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, ethyl orthosilicate, propyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane and octyltrimethoxysilane, and the purity of the alcohol crosslinking agent is ≥99%.

7. A high performance solar structure sealant according to claim 6, characterized in that: The silane coupling agent is at least one of γ-aminopropyltriethoxysilane, γ-aminoethylaminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, and γ-(2,3-epoxypropoxy)propyltrimethoxysilane.

8. The high-performance solar structural sealant according to claim 7, characterized in that: The catalyst is at least one of dibutyltin dilaurate, dioctyltin dilaurate and dibutyltin dicaprate; the pigment is titanium dioxide paste or carbon black paste.

9. A method for preparing a high-performance solar structural sealant according to any one of claims 1 to 8, characterized in that: The steps include: Step 1, mixing hydroxyl-terminated polydimethylsiloxane, calcium carbonate and fumed silica and stirring to obtain a mixture; Step 2: the mixed material obtained in step 1 is discharged after being shoveled, dehydrated at high temperature, and stirred evenly to obtain a single-component glue base material; Step 3: Evenly stir the base material in step 2 with the cross-linking agent, the silane coupling agent, the polyalkoxy water-resistant additive with a long alkyl side chain, and the catalyst to obtain a high-performance solar structural sealant.

10. The method for preparing a high-performance solar structural sealant according to claim 9, characterized in that: The stirring processes in step 2 and step 3 are both carried out under vacuum conditions; in step 3, the preparation method of a polyalkoxy water-resistant additive having a long alkyl side chain comprises the following steps: S1. Add appropriate amount of toluene and catalyst chloroplatinic acid into hydrogen-containing silicone oil; S2. Raise the temperature to 100-110°C, slowly drop vinyltrimethoxysilane and 1-tetradecene under stirring or reflux; S3. Separation: remove the solvent by distillation under reduced pressure.